THE EFFECT OF USING WEB TOON STORY AS TEACHING MATERIAL TOWARDS THE STUDENTS’ WRITING ABILITY - Deri Sis Nanda; Dedi Kurniawan; Susanto Susanto (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2019)
This paper reports a study on the effect of using web toon story towards students’ ability. The study was conducted at the second grade of SMK N 1 Gunung Pelindung, Lampung Timur. It used random sampling technique to select the sample. Pre-test and post-test were used as the research instrument to collect the data. In the quantitative method, the students as the subjects of participants were divided into two groups: experimental group (N=30) and control group (N=30). The data was analyzed by using t-test analysis showing that the experimental and control group mean scores in the pre-test were not significantly different. It can be seen that t-count was lower than t-table (0.229 < 2.002) and the sig.2-tailed value is higher than sig. level (0.820 > 0.05). Therefore, both experimental and control groups have the same level of writing ability before treatment. However, in the post-test, the mean score of experimental group is higher than control group. T-count is higher than t-table (10.706 > 2.002) with the sig.2-tailed value is lower than sig. level (0.000 < 0.005). Therefore, the null hypothesis (Ho) was rejected and the alternative (Ha) was accepted. It means that there was the effect of using web toon story as teaching material towards the students’ writing ability.